Drug Related Problems (DRP's) Analysis of Antipsychotics Use in Schizophrenia Patients at Mental Hospitals of Southeast Sulawesi Province in 2021 - Restu Nur Hasanah Haris; Rifa’atul Mahmudah; Vica Aspadiah; Nur Fitriana Muhammad Ali; Wa Ode Masrida; Nursyam Nursyam (Program Studi Farmasi Universitas Mandala Waluya, 2023)
Schizophrenia is a psychiatric disorder with a high incidence at the Mental Hospital of Southeast Sulawesi. Problems related to the use of drugs that are often encountered in hospitals are inaccuracies in drug administration, inaccurate dosing and drug abuse. This problem can affect the success of therapy. This study aims to determine the pattern of drug use and the prevalence of Drug Related Problems (DRPs) in Schizophrenia patients based on the correct dosage parameter. This research is an observational type with a cross sectional design. The duration of the study was 1 month taking into account the inclusion and exclusion criteria.. Patients with a diagnosis of schizophrenia, aged >17 years and have a complete medical record are the inclusion criteria whereas patients with incomplete medical records, death status/forced to go home and still being treated are exclusion criteria. The total number of samples analyzed was 250 patient medical records. The results showed that the majority of Schizophrenia patients at the Mental Hospital of Southeast Sulawesi Province were male (80%) with an age range of 20-45 years (71.6%). The last education level is in the medium category (65.2%). Based on the diagnosis of the type of schizophrenia, the patient was in the category of paranoid schizophrenia (51.6%) with positive symptoms (74.8%). The pattern of psychotic drug use used by Schizophrenia patients at the Mental Hospital of Southeast Sulawesi Province in 2021 is a single pattern and the most widely used single drug combination pattern is risperidone (atypical) (35.6%) and a combination pattern, namely chlorpromazine + risperidone (typical +atypical) (27.2%). The prevalence of DRP's based on the correct dose is 0%. DRP's did not occur for the use of antipsychotic drugs in Schizophrenia patients at the mental hospital of Southeast Sulawesi Province in 2021.